Knowledge as a (non-factive) mental state - Bricker Adam Michael (Netherlands, 2025)
The thesis that knowledge is a factive mental state plays a central role in knowledge-first epistemology, but accepting this thesis requires also accepting an unusually severe version of externalism about the mind. On this strong attitude externalism, whether S is in the mental state of knowledge can and often will rapidly change in virtue of changes in external states of reality with which S has no causal contact. It is commonly thought that this externalism requirement originates in the factivity of knowledge. However, despite a number of recent defenses of non-factive accounts of knowledge, epistemology has yet to consider whether a non-factive approach might produce a version of the mental state thesis that can avoid strong externalism. Here I do just that, exploring how three different proposals for weakening factivity might be adapted to theories of knowledge as a non-factive mental state. Contrary to what we might expect, however, none of these proposals are compatible with anything close to attitude internalism about knowledge—or even a substantially weaker externalism. All told, the widespread view that wraps up the severe externalism required for knowledge to be a mental state in factivity is mistaken. Knowledge’s external-world connection runs far deeper than the factivity constraint.